Nutritional Status is Not Associated with Diarrhea Duration or Weight Recovery in Young Children in a Resource-Poor Setting. (4th October 2017) - Lamb, Molly; Melgar, Mario; Calvimontes, Diva M; Asturias, Edwin J; Contreras-Roldan, Ingrid; Dominguez, Samuel; Berman, Stephen; Gaensbauer, James
Abstract: Background: Young children in low and middle income countries suffer from frequent diarrheal illnesses that contribute to acute and chronic malnutrition. It is unclear whether malnourished children recover more slowly from diarrheal illness, due to weakened immunity or a compromised intestinal brush border. Thus, we explored associations between chronic and acute malnutrition, diarrhea duration and weight recovery in young Guatemalan children. Methods: From March 2015 to January 2016, 301 children age 6–35 months from rural ( N = 166) and urban ( N = 135) Guatemala who sought clinical care for acute non-severe non-bloody diarrhea were followed prospectively for diarrhea resolution as part of a clinical trial. Severely malnourished children (WHO weight-for-height z-scores (WFLZ) <-3) were excluded. Height, weight, treatments prescribed, and stool tests of 22 diarrheal pathogens were collected at enrollment. Height and weight were also collected 2 and 4 weeks after rehydration. Cox proportional hazards regression was used to model the effect of WHO height-for-age z-scores (HAZ, chronic malnutrition proxy) and WFLZ (acute malnutrition proxy) on diarrhea duration and weight recovery. Analyses were adjusted for age, treatment prescribed, number of pathogens, and presence of parasites; and stratified by urban vs rural due to demographic and treatment differences. Results: In the rural site, 33% of children had a HAZ below -2, and 22% had a WFLZ between -2 and -3. In separate survival analyses, neither low HAZ (Hazard Ratio (HR): 1.08, 95% Confidence Interval (CI): 0.76–1.54) nor low WFLZ (HR: 1.07, CI: 0.72–1.61) were associated with diarrhea duration. In the urban site, 33% of children had a HAZ below −2, and 10% had a WFLZ between −2 and −3. Again, neither low HAZ (HR: 1.21, CI: 0.68–2.17) nor low WFLZ (HR: 1.43, CI: 0.74–2.79) were associated with diarrhea duration. Neither low HAZ nor low WFLZ were associated with weight recovery at 2 or 4 weeks in either site. Conclusion: In children with a single episode of infectious diarrhea, moderate malnutrition does not affect diarrhea duration or short-term weight recovery. Measures to prevent recurrent infection in such children may be more important to long-term nutritional status than more aggressive acute diarrheal treatment. Disclosures: E. J. Asturias, Takeda Pharmaceuticals: Consultant and Grant Investigator, Grant recipient